Psychometric Properties of the Bangla Version of the Big Five Personality Inventory-10 (Chittagong University Journal of Biological Sciences, 2024)
Shorter assessing instrument for measuring psychological construct is on the rise in recent years. Personality measuring instruments are not an exception to this. The present study aimed to assess the psychometric properties of the Bangla version of the Big Five Personality Inventory–10 (BFI-10). This instrument was translated into Bangla and back-translated into English by following the International Test Commission's guidelines. After the pretest, the translated version of this scale was administered on a sample of 372 students. Psychometric properties were estimated through both classical test theory and item response theory. Findings revealed that the Bangla version of this scale had sufficient inter-item correlations, inter-factor correlations, test-retest reliability, non-DIF contrast, and Rasch model fit. This translated scale would be applicable to assess the personality of the Bangladeshi people and fulfill the demand fora short version of the personality assessment scale in the Bangladesh context.The Chittagong Univ. J. B. Sci.,Vol. 10(1&2):71-80, 2020